(untitled) (Pedagogy of Higher and Secondary Education, 2016)
Budanova L. G. Trends analysis of organization and performing of future pharmacists’ academis achievements quality diagnostics. Diagnostics of academis achievements quality of pharmaceutical students in foreign higher education establishments has been analyzed. It has been observed tendencies of future pharmacists’ professional training and grounded ways of its improving in terms of modernization of higher pharmaceutical education in Ukraine. The strategic orientations of higher pharmaceutical education are aimed at improving the professional education quality, so the quality of future pharmacists’ knowledge is determined by their fundamentality, depth and relevance in the future professional activity. The expediency of test-control using for future pharmacists’ basic knowledge diagnostics has been proved. In the context of understanding the importance of pharmacist profession in society, specialist training quality is a fundamental and open issue. It impacts on the quality of health care and patient care. Today training of pharmacists is essential as this profession is socially important for preservation and promotion of health, and disease prevention. The system of higher education in medical and pharmaceutical establishments consists of a number of interrelated elements, among which monitoring and assessment are important. The most widely spread methods among diagnostics tools are monitoring and assessment by testing as in European countries and in Ukraine. Test control – is a universal form of basic knowledge control, due to it the diagnostics and evaluation of knowledge is carried out objectively, quickly, covers all course material, gives true results. Modern diagnostic tools for basic knowledge diagnostics in pharmaceutical education system should be considered in the context of fundamental changes taking place in higher pharmaceutical education in Ukraine.